1998
DOI: 10.1029/98tc02764
|View full text |Cite
|
Sign up to set email alerts
|

Northeastward growth of the Tibet plateau deduced from balanced reconstruction of two depositional areas: The Qaidam and Hexi Corridor basins, China

Abstract: Abstract.We address the problem of late Cenozoic uplift, erosion, and growth of northeastern Tibet by reconstructing, from isopach maps and drill holes, the vol-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
302
2
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(332 citation statements)
references
References 31 publications
18
302
2
4
Order By: Relevance
“…However, the rates of shortening for the individual faults decreases to the east, as demonstrated by the rates for the north-vergent Tanghenan and Zhangye thrusts. Interestingly, Meyer et al (1998) estimated a shortening rate of 2.1 ± 0.6 mm/yr for a thrust in the piedmont of the Taxueh Shan., Taken together with the shortening rates for the Tanghenan and Zhangye thrusts the Taxueh Shan rate, though not confirmed by quantitative dating, would yield an eastwardly decreasing shortening rate consistent with models for the propagation of the ATF and asymmetric growth of the plateau via associated thrusting (Métivier et al, 1998;Meyer et al, 1998). …”
Section: While There Are Numerous Additional Thrusts Between the Qaidmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the rates of shortening for the individual faults decreases to the east, as demonstrated by the rates for the north-vergent Tanghenan and Zhangye thrusts. Interestingly, Meyer et al (1998) estimated a shortening rate of 2.1 ± 0.6 mm/yr for a thrust in the piedmont of the Taxueh Shan., Taken together with the shortening rates for the Tanghenan and Zhangye thrusts the Taxueh Shan rate, though not confirmed by quantitative dating, would yield an eastwardly decreasing shortening rate consistent with models for the propagation of the ATF and asymmetric growth of the plateau via associated thrusting (Métivier et al, 1998;Meyer et al, 1998). …”
Section: While There Are Numerous Additional Thrusts Between the Qaidmentioning
confidence: 98%
“…The northeastward propagation of the leftlateral Altyn-Tagh Fault, and the regional northeastward elevation decrease (~3000 m to 1200 m a.s.l. ), suggest a close relationship between sinistral faulting and thrusting in which sinistral motion along the ATF is transferred to the active thrust faults (Métivier et al, 1998;Meyer et al, 1998;. The rates of both sinistral slip on the ATF and shortening across the thrusts should decrease due to the eastward transformation of lateral slip to shortening.…”
Section: Geomorphic Rates Of Thrusting and Crustal Shorteningmentioning
confidence: 99%
“…1). The remarkably low relief of the Tibetan Plateau has been explained by the development of an internal drainage system and the progressive filling of intramontane basins by sediments eroded from the adjacent mountains (Métivier et al, 1998, Sobel et al, 2003Liu-Zeng et al, 2008). Apart from the sedimentcovered areas resulting from the process described above, older low-relief surfaces that are developed in bedrock have been documented in the southeastern Tibetan Plateau (Clark et al, 2004) and in the Lhasa terrane of southern Tibet (Strobl et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The Qilian Mountain raised at ~5.3 Ma [11] and began to entirely and rapidly raise at ~3.6 Ma. Sun et al [13] suggested that the late Cenozoic tectonic deformation, marked by folding and thrusting, occurred at ~5.3 Ma.…”
Section: Asian Monsoon Evolutionary History and Phased Himalaya-tp's mentioning
confidence: 99%